WORKSHOP DAN PENDAMPINGAN TUKANG PLESTER DAN ACIAN DI DESA BINAAN UTEUNKOT KOTA LHOKSEUMAWE - Syibral Malasyi; Mukhlis; Fasdarsyah; Teuku Muda Hafli; M. Fauzan; David Sarana (LPPM Universitas Al Muslim, 2023)
Uteunkot Village is one of the villages in Lhokseumawe City and is a fostered village of Malikussaleh University. Over time, the increase in population has had an impact on changes in land use in Uteunkot Village, initially there was a lot of idle and unused land, but the increasing number of requests for residential houses has increased the number of residential buildings in Uteunkot Village. The increase in residential houses in Uteunkot Village was not matched by builders, especially plasterers and wall coating, to spruce up the appearance of the village's residential houses. Plaster work is covering walls (concrete, red brick, brick, light brick) with a layer of sand mixed with cement. Meanwhile, the wall coating job is to coat the plaster that has been attached to the wall with cement to smooth the surface. Therefore, there was a need for training in the plaster and coating process for builders in Uteunkot Village. The method used in this activity was by counseling in the form of providing theoretical view of the positive impact in the field of plaster and building coating. Then, proceed with a good and correct plastering and wall coating process.